Sexually dimorphic brain and behavioral asymmetries in the neonatal rat. - Ross, D A (1981)
The 2-deoxy-D-glucose method was used to study asymmetries in cerebral metabolic activity in neonatal rats. Left-right asymmetries in 2-deoxy-D-glucose uptake were observed in hippocampus, diencephalon, cortex, and medulla-pons: 2-deoxy-D-glucose incorporation was greater in right hippocampus, right diencephalon, left cortex, and left medulla-pons. These asymmetries occurred only in females. We also observed neonatal asymmetries in tail position that, in both sexes, were predictive of adult turning preferences; females had right-sided biases in both neonatal and adult characteristics. Collectively these data indicate that cerebral lateralization is sexually dimorphic and is present at birth.